Covering Body, Uncovering Identity: Chinese Muslim Women's Vocabularies of Dress, Based on Fieldwork in Northwest and Central China. (31st May 2016) - Jaschok, Maria; Ke, Man
Abstract : This ethnography of Chinese female Islamic dress serves to explore the way that Chinese Muslim women of different generations and backgrounds both seek accommodation and meaning within the gendered modernity of a rapidly changing Chinese (non-Muslim) society and also strive for transcending authenticity as they translate Islamic prescriptions into personal conduct. The authors present defining characteristics of local versions of the Chinese hijab within the rich diversity of China's Muslim contexts and across complex religious landscape of an ethnic religion. Building on the work of international Islamic feminist scholars, the concept of the hijab is explored in terms of three dimensions, incorporating the visual dimension as shielding from the public gaze; the spatial, demarcating the public from the private sphere; and the ethical, informing thought and ideas.